Analisis Perbandingan Certainty Factor dan Dempster Shafer Dalam Diagnosis Penyakit Porfiria Menggunakan Metode Perbandingan Eksponensial - Rizky, Firahmi; Zulham, Zulham; Nasyuha, Asyahri Hadi; Elyas, Ananda Hadi; Kartadie, Rikie (Forum Kerjasama Pendidikan Tinggi, 2023)
Porphyria refers to a group of genetic disorders that affect the metabolism of porphyrins in the body. Porphyrin itself is a molecule that plays a role in the synthesis of hemoglobin, which functions as a carrier of oxygen in the blood. Disturbances in porphyrin metabolism can lead to the accumulation of porphyrins or their precursors, which in turn can produce a variety of symptoms. Porphyria comes in many forms, including acute porphyria and skin porphyria, each with its own unique symptoms. Nervous system and skin problems are common in porphyria patients, and if not treated properly, their health condition can deteriorate. A unique approach is needed to provide answers to this problem because it is still challenging to develop practical ways to address the problems experienced by patients. Certainty Factor and Dempster Shafer methods are two techniques that are widely used in the field of disease diagnosis today, where expert systems are often applied. But building expert systems in multiple disciplines is difficult due to uncertainty. Therefore, it is important to research and distinguish the many ways that these systems can be built. The exponential comparison approach is one of the most straightforward comparison techniques and helps minimize bias in the analysis process. To identify candidiasis in humans, this study attempted to apply, evaluate, and compare the two methodologies, as well as compare the results with the exponential comparison method. Comparative findings suggest that the Dempster Shafer technique provides a more precise diagnosis of porphyria